EFEK EKSTRAK ALOE VERA TERHADAP CANDIDA ALBICANS YANG DIISOLASI DARI RONGGA MULUT PENDERITA HIV/AIDS DENGAN TEKNIK TUBE DILUTION : EFFECT OF ALOE VERA LEAF EXTRACT TO CANDIDA ALBICANS ISOLATED FROM ORAL CAVITY OF HIV/AIDS PATIENTS BY TUBE DILUTION TECHNIQUE - Elizabeth Fitriana Sari; Gus Permana Subitha (TALENTA, 2011)
Oral candidiasis is the third major opportunistic infection in people with HIV/AIDS. The antifungal has a very important role to prevent candidemia. But the use of antifungal has developed resistancy, for this reason it is important to find other high potent and cost effective antifungal. In this study Aloe vera was choosen because of its beneficial properties which has already been proven scientifically. The objective of the study was to investigate antifungal effect by finding the minimal inhibitory concentrations (MICs) and minimal fungicidal concentrations (MFCs) of Aloe vera leaf to Candida albicans isolated from oral cavity of HIV/AIDS patients, and to Candida albicans ATCC 10231 strain as the control group. Ethanol was used for the extraction of the leaf after obtaining the gel from it. MICs and MFCs were tested by tube dilution technique. Eight identified samples of Candida albicans isolated from oral cavity of HIV/AIDS patients. The result showed that from 3 samples had MIC 25%, and 4 samples 50%. MFC showed 1 sample in 12.5%, 3 samples in 100%, but 4 samples could still grow in 100% concentration with different number of colony forming units. As the control group, Candida albicans ATCC 10231 showed MIC in 25% and MFC in 75%. In conclusion, aloe vera plants seem to have promising role to cure oral candidiasis in HIV/AIDS patients because of its antifungal and immunomodulatory properties.